2020
DOI: 10.1371/journal.pone.0234771
|View full text |Cite
|
Sign up to set email alerts
|

A herbicide resistance risk assessment for weeds in wheat and barley crops in New Zealand

Abstract: We estimated the risk of selecting for herbicide resistance in 101 weed species known to occur in wheat and barley crops on farms in New Zealand. A protocol was used that accounts for both the risk that different herbicides will select for resistance and each weed's propensity to develop herbicide resistance based on the number of cases worldwide. To provide context we documented current herbicide use patterns. Most weeds (55) were low-risk, 30 were medium-risk and 16 high-risk. The top ten scored weeds were E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…minor , and S . media [ 6 ]. Bromus catharticus was resistant to ALS-inhibiting herbicides in this study, a first globally [ 5 ], but identified as medium to low risk by Ngow et al [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…minor , and S . media [ 6 ]. Bromus catharticus was resistant to ALS-inhibiting herbicides in this study, a first globally [ 5 ], but identified as medium to low risk by Ngow et al [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, herbicide resistance is common in arable crops such as wheat (344 cases and 83 species) and barley (87 cases, 47 species) [ 5 ]. Based on worldwide patterns of resistance, Ngow et al [ 6 ] identified 16 species with a high risk of developing resistance in New Zealand wheat and barley fields (eight were grasses Avena fatua L., A . sterilis L., Digitaria sanguinalis (L.) Scop., Echinochloa crus-galli (L.) P.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical control using herbicides is mostly favored as they offer efficient, cost-effective and reliable weed control contributing to high seed yields. Herbicides are generally providing a threefold to fourfold economic return compared to other weed control measures (Ngow et al 2020). Studies have shown that herbicide application effectively controls the weeds and can increase the seed yield by 43.2 to 86.9% (Voevodin andBorisenko 1981 andPatel et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Herbicides from these groups were commonly applied for weed control in wheat [5,48]. According to Ngow et al [49], synthetic auxins were used most frequently in weed control in cereals. However, despite their frequent use in cereals, active substances from this group cause relatively little resistance, and they are included in the group of medium risk resistance [41].…”
Section: Discussionmentioning
confidence: 99%
“…Florasulam (HRAC 2), tribenuron (HRAC 2) and aminopyralid (HRAC 4) were also often used by farmers. Diflufenican was one of the substances used most frequently in the research presented by Ngow et al as well [49]. Considering that ALS inhibitors are among the herbicides that are very prone to resistance selection, a reduction in their use is an important recommendation [4,41].…”
Section: Discussionmentioning
confidence: 99%